PENGARUH BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN HUMAN CAPITAL MANAGEMENT PT PERUSAHAAN GAS NEGARA TBK - Nurshadrina, Nazwa; Rahmawati, Siti (Universitas Nusa Cendana, 2024)
In the era of globalization, the quality of human resources is the key to success in competing internationally. The IMD World Talent Ranking 2023 report shows that Indonesia is ranked ninth in Asia, but with a score of 51.13 out of 100, Indonesia is still ranked 47 out of 64 countries, signifying a big challenge in improving the quality of human resources at the global level. PT Perusahaan Gas Negara Tbk (PGN), the largest natural gas transmission and distribution company in Indonesia, applies AKHLAK values to create a high work culture. Despite an increase in job satisfaction based on annual surveys, a decrease in the HSH 2023 Maturity Level score indicates a lack of understanding of AKHLAK values. This study analyzes the influence of organizational culture and job satisfaction on the overall performance of PGN HCM employees using descriptive analysis methods, and SEM-PLS. The research was conducted from March to May 2024 with a saturated sampling approach and involved 53 respondents. The results showed that organizational culture has no effect on employee performance while job satisfaction affects employee performance. Keywords: Job Satisfaction; Organizational Culture; Performance